Diversification history and hybridisation of Dacrydium (Podocarpaceae) in remote Oceania - Keppel, Gunnar; Prentis, P.; Biffin, E.; Hodgskiss, P.; Tuisese, S.; Tuiwawa, V.; Lowe, A. (CSIRO Publishing, 2011)
We examined evolutionary relationships, hybridisation and genetic diversity in species of Dacrydium (Podocarpaceae) in Remote Oceania, where it is restricted to New Caledonia and Fiji. We used cpDNA sequence (trnL–trnF) data to construct a phylogeny and estimate taxon divergence by using a relaxed molecular clock approach. The phylogeny was verified using allozymes, which were also used to investigate genetic diversity of all species and the hybridisation dynamics of two endangered species, D. guillauminii and D. nidulum. Our results suggested that Dacrydium species in Remote Oceania form a monophyletic group that arose and diversified within the last 20 million years through long-distance dispersal and a range of speciation mechanisms. Whereas we detected no hybridisation between the Fijian species D. nausoriense and D. nidulum, we confirmed hybridisation between D. guillauminii and D. araucarioides in New Caledonia and determined introgression to be assymetric from the widespread D. araucarioides into the rare, restricted-range species D. guillauminii. In addition, D. guillauminii had lower genetic diversity than did the other species of Dacrydium studied, which had genetic diversity similar to that of other gymnosperms. Our results provided evidence for the recent and complex diversification of Dacrydium in Remote Oceania. In addition, low genetic diversity of and introgression from D. araucarioides, are of grave concern for the conservation of D. guillauminii.